The Development of Digital Book Media Materials for Asean Countries Learning in Elementary School - Agita Ayu Diah Pitaloka; Rd. Deti Rostika; Yona Wahyuningsih (Universitas Tanjungpura, 2022)
This research is motivated by optimizing ASEAN material in sixth grade Elementary School in social studies learning through digital book media, the use of digital book media is used because of the lack of use of learning media during teaching and learning activities, then the use of media can provide interest and motivation to learn in students with a good display. interesting. The purpose of this study is to develop digital book media for ASEAN countries, and to find out the results of the feasibility of the media through experts, teacher users and sixth grade elementary school students. The method used in this research is the D&D method with the ADDIE research procedure. Based on the research results, there are validation assessments from various experts, including social studies material experts, media experts, and linguists. Based on the results of the assessment of material experts, media experts, and linguists, it can be concluded that the Digital Book Media of ASEAN Countries is in the